Effect of Annealing Treatment on the Optical Properties of Zinc Oxide (ZnO) thin film prepared by MOCVD - Iis Nurhasanah; Priyono Priyono; Wilson W Wenas (Journal of Mathematical and Fundamental Sciences, 2001)
The annealing treatment of ZnO thin film at various temperatures was performed. The effect of this treatment on the optical properties of ZnO thin film were investigated in order to apply this film to optoelectronic devices. The optical transmittance spectra  were measured and it was found that the transmittance in UV-VIS region decreased with annealing temperature . The loss of light is mainly due to  the increase of carrier density, resulting from increased oxygen vacancies during the annealing process at 300°C. It was also found that the absorption edge shifted to lower energy when the film was annealed at 300°C in air.